Dentinal tubule occlusion effects of dipotassium oxalate and diode laser combination: a single-blind in vitro study - Ömer Birkan Ağralı; Eser Elemek; Canan Güler Kılıç; Semra Ünal; Çiğdem Doğan; Hatice Selin Güngörmek; Hare Gürsoy; Leyla Kuru (BMC Oral Health)
Abstract Background Dentin hypersensitivity (DH) affects many patients. Various therapeutic options have been devised to alleviate this condition by achieving dentinal tubules (DT) occlusion. This research aimed to investigate the effects of dipotassium oxalate-containing mouthwash, diode laser and their combination on DT occlusion. Methods Forty dentin samples were obtained from 20 human single-rooted third molars, 40 dentin specimens were obtained, and exposed DT were created in vitro. They were assigned into four groups: Group 1 (n = 10), the control group where no treatment was applied; Group 2 (n = 10), a mouthwash with a 1.4% dipotassium oxalate was applied twice for 60 s during a 5-day period in a shaker at 100 rpm; Group 3 (n = 10), a combination of the same mouthwash and an 810 nm diode laser at an output power of 0.25 W in continuous mode was applied for 60 s without contact at a distance of 3–4 mm; and Group 4 (n = 10), only a diode laser with the same protocol was applied. Occlusion of the DT was observed by scanning electron microscopy. Results The analysis revealed occlusion of the DT in all treatment groups; however, the effects were more pronounced in the combined treatment group (Group 3). Compared with the test groups, the control group had significantly more open DT in 100 µm2 (p < 0.01). The difference between the Group 2 and Group 4 was not significant (p > 0.05). Conclusion DT occlusion was achieved via the use of a mouthwash containing 1.4% dipotassium oxalate and an 810 nm diode laser. However, the combination resulted in the greatest results and therefore may be utilized in individuals with DH.